Cnotliwy Chrześcijanin czy Sceptyczny Chemik? Robert Boyle wobec dylematu: wyznaniowość a naukowość - Kazibut, Radosław (Przegla̜d religioznawczy, 2013)
Robert Boyle is the author of the original concept of mediation between the spheres of religious believe and scientific thought. The article presents Robert Boyle’s selected topics of epistemology that illustrate his points of view on the issue of the relationship between scientific knowledge and faith. This association appears in the context of his deliberations on sources of human knowledge, the defence of the rule - final causes of natural things, and limits of reason. In the summary of the article, Boyle’s idea of the relation between science and faith is compared to the NOMA proposal and the Intelligent Design.